2018
DOI: 10.21273/horttech04114-18
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Sensor-based Automated Irrigation in Commercial Floriculture Production: A Case Study

Abstract: A soil moisture sensor-based automated irrigation system was trialed in a commercial floriculture greenhouse to determine what benefits these types of systems may offer to herbaceous ornamental producers. Water use, crop quality and growth, and grower behavior toward adoption of the new technology were monitored, when all decision making related to system operation was carried out by the grower. Two cultivars of poinsettia (Euphorbia ×pulcherrima) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Water applied in Sensor LM 35 automated irrigation-based system was lower than conventional system and plant yield was higher in automated irrigation system as compared to conventional system [16]. VegApp and SMS-based irrigation regimes applied 15% and 29% less water, respectively, than the WB method in watermelon [17,18].…”
Section: Nano Sensor With Drip In Crop Productionmentioning
confidence: 99%
“…Water applied in Sensor LM 35 automated irrigation-based system was lower than conventional system and plant yield was higher in automated irrigation system as compared to conventional system [16]. VegApp and SMS-based irrigation regimes applied 15% and 29% less water, respectively, than the WB method in watermelon [17,18].…”
Section: Nano Sensor With Drip In Crop Productionmentioning
confidence: 99%
“…The study reported a water use reduction of approximately 50% when compared to grower-controlled irrigation. The same sensor system was trialed previously by Wheeler et al [ 5 ] in a floriculture greenhouse.…”
Section: Sensing and Automation Technologies For Ornamental Cropsmentioning
confidence: 99%
“…Greenhouses are typically enclosed environments where growth conditions (e.g., lighting, temperature, humidity, and irrigation) can be controlled [ 4 ]. Rapidly increasing production cost due to the increased labor expense, difficulty in obtaining skilled labor, and inappropriate application of agricultural resources are rising concerns for the ornamental industry [ 5 , 6 ]. Operations such as planting, growing, and harvesting nursery crops are heavily dependent on labor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be attributed to the fact that plants sold to big-box stores and multiple location garden centers (such as bedding plants and flowering potted plants) demand more labor input, particularly from low-skilled temporary workers. As suggested by Wheeler et al (2018), automation and mechanization were potential means for horticultural producers to overcome labor challenges and increase profitability with tightening labor supply throughout the United States.…”
Section: Factors Influencing Market Shares Of Major Wholesale Market ...mentioning
confidence: 99%